Pengenalan Konsep Literasi Keuangan kepada Siswa Sekolah Menengah Pertama di Desa Montong Ajan, Lombok Tengah - Putri, Baiq Krisnina Maharani; Aptasari, Fety Widianti; Hastuti, Ely Windarti; Mujahidi, Khairul (Tintamas: Jurnal Pengabdian Indonesia Emas, 2025)
This community engagement initiative was implemented to enhance financial literacy among students of SMP Islam Tanwirul Qulub Sengketan, located in Montong Ajan Village. The program was motivated by observations showing that many junior high school students still lack basic knowledge of financial concepts such as saving, budgeting, and understanding the value of money. Activities were carried out using a participatory approach, actively involving students throughout the process. The program was further enriched with interactive games and a social service component, including the distribution of school supplies and other essential educational materials. Through these activities, students at SMP Islam Tanwirul Qulub gained a clearer understanding of personal financial concepts, including the importance of saving, distinguishing between needs and wants, and managing their pocket money wisely.